Staying With the Trouble: Grapplings With the More-Than-Human in a Qualitative Inquiry Course. (January 2020) - Nxumalo, Fikile; Cook, Courtney; Rubin, Jessica Cira; Hendrix Soto, Aimee; Cedillo, Stacia; Scott, Michael
This article attends to the possibilities that emerged from pedagogical invitation to the more-than-human in a qualitative inquiry course. We focus on the situated ethical and (micro)political grapplings that emerged from paying attention to the more-than-human alongside asymmetrical human and more-than-human lifeworlds. Our orientation toward the ethical and (micro)political is enacted through visual, poetic, and narrative storytelling that attempts to make visible what emerged for the students' research and their becomings as qualitative inquirers in relation with course pedagogies. Our storytelling enacts a feminist practice that "stays with the trouble" stirred up by decentering the human while remaining accountable to enduring systemic, colonial, racialized, and gendered presences. While the particular lines of flight enacted by the pedagogical invitations in the course differed for each student, they come together in underlining the mattering of pedagogical and inquiry-based attunements toward the more-than-human within unequal worlds.